Phenotypic Variation and Growth Performance of offsprings Betta splendens Generations from Crown Tail and Double Tail Hybridization - Darmawan Setia Budi; Diki Firdiansyah; Akhmad Taufiq Mukti (Journal of Aquaculture Science, 2026)
Betta fish (Betta splendens) are ornamental fish with a long history of domestication and selective hybridization aimed at enhancing phenotypic variation. This study aimed to evaluate the effect of reciprocal hybridization between crowntail (CT) and doubletail (DT) strains on the phenotypic variation of the offspring. Four breeding combinations were applied: TA (CT♂ × CT♀), TB (DT ♂ × DT ♀), TC (CT♂ × DT♀), and TD (DT♂ × CT♀), representing intra- and inter-strain crosses between crowntail (CT) and doubletail (DT) broodstock. The experiment was conducted for 75 days, from spawning to juvenile rearing. Observed parameters included meristic and morphometric characteristics, coloration, growth performance, and survival rate of the offspring. The results indicated that reciprocal hybridization significantly affected the observed parameters. Male and female offspring from treatments TC (0.99681) and TD (0.99709) showed closer correlations with control TA (CT♂ × CT♀) in meristic characters. In terms of morphometric traits, male offspring from treatments TC (0.99054) and TD (0.98765) were more closely associated with treatment TA, whereas female offspring showed a stronger correlation with treatment TD. Hybridization between crowntail and doubletail white platinum strains produced novel color variations, including platinum-red and platinum-silver phenotypes. Furthermore, the growth performance of reciprocal hybrids differed significantly (p < 0.05) from that of the control groups. These findings demonstrate that reciprocal crossing between crowntail and doubletail strains influences phenotypic expression in offspring.